Benzo[a]pyrene immunogenetics and immune archetype reprogramming of lung. (November 2021) - Abd El-Fattah, Eslam E.; Abdelhamid, Amir Mohamed
Abstract: Overexposure to carcinogenic precursor, benzo[ a ]pyrene [BaP], modulates the lung immune microenvironment. The present review seeks to elucidate novel pathways behind the tumor effect of BaP in the lungs, emphasizing immunomodulatory mediators and immune cells. In this review, BaP reprograms lung immune microenvironment through modulating transforming growth factor-beta (TGF-β), programmed cell death 1 (PD-1), cytotoxic T lymphocyte antigen-4 (CTLA-4), Interleukin 12 (IL-12), indoleamine 2, 3 dioxygenase (IDO), forkhead box protein P3 (FOXP3) and interferon-gamma (IFN-γ) levels. Moreover, BaP modulated lung immune cellular architecture such as dendritic cells, T cells, Tregs, macrophages, neutrophils, and myeloid-derived suppressor cells (MDSCs). All mentioned changes in immune architecture and mediators lead to the induction of lung cancer.